Efect of acacia (Acacia decurrens) in the development and production of grass aubade, Botana - Torres C., Leidy Lorena; Aragón, Livia; Silva P, Amanda (Revista de Ciencias Agrícolas, 2009)
The research aimed at improving the management of this system silvopastoril in high altitude areas, was conducted in the Central Experimental Botany, University of Nariño, located at 1 ° 09'28 .3''N, 77°16'29.5"O. The objective was to measure the efect of Acacia decurrens on some of the grass Aubade Lolium multiflorum Lam height of plants, green fodder, leaf: stem and percentage of dry matter. Differences were statistically significant (p <0.01) for all variables analyzed. Grass Aubade Lolium multiflorum Lam planted at distances of 0 at 0.5 and at 0.5 to 1 m above the highest values offered Acacia decurrens plant height (AP) and green fodder (FV) with values of 58.7 and 50.7 cm and 60.8 and 53.5 ton/ha, percentage of dry grass (%MS) ranged between 9.06 and 4.97 when it was planted of 1.5 at 2 and 0.5 at 1 m, was greater leaf: stem (RH:T) grass planted at 0 m under the influence of the tree with a value of 4.20. There was a positive trend between % MS and the RH: T and the negative % MS to the production of FV and AP. Keywords: grass, tree, green fodder, dry matter, leaf: stem